Analisis Faktor Yang Mempengaruhi Pendapatan Peternak Itik Petelur Di Desa Pematang Johar Kabupaten Deli Serdang - Herdian Herdian; Gustami Harahap; Khairul Saleh (Jurnal Ilmiah Pertanian ( JIPERTA), 2021)
This study aims to determine what are the analysis of the factors that influence the income of laying duck farmers. The Purpose of this Research: (1) To find out what factors influence the income of laying ducks. (2) To find out how much the income of laying duck farmers. This research was conducted in September 2019 until November 2019. The sampling method was saturated or saturated, in this study the sample used was 32 laying duck breeders. The analytical method used is multiple linear regression with SPSS 21 tools. Results of this study: (1) the results of the study that the Fcount value is 399,130 and the significance value is 0,000 less than 0.05 or Fcount 399,130 greater than Ftable 2,73. For the t test, venture capital partially has significant effect on the income of laying ducks, the business experience partially has a significant effect on the income of laying ducks, the number of livestock partially has a significant effect on the income of laying ducks, cattle fairs partially has a significant effect on the income of laying ducks, . (2) total cost of receiving is Rp. 391.550.000 with an average of 12.235.937, the total production cost is Rp.300.432.500 with an average of 9.388.515, and the total cost of income is Rp.319.380.000 with an average of 9.980.625.